Multiple causal variants underlie genetic associations in humans - Abell, Nathan S; DeGorter, Marianne K; Gloudemans, Michael J; Greenwald, Emily; Smith, Kevin S; He, Zihuai; Montgomery, Stephen B (Science (American Association for the Advancement of Science), 2022)
Associations between genetic variation and traits are often in noncoding regions with strong linkage disequilibrium (LD), where a single causal variant is assumed to underlie the association. We applied a massively parallel reporter assay (MPRA) to functionally evaluate genetic variants in high, local LD for independent cis-expression quantitative trait loci (eQTL). We found that 17.7% of eQTLs exhibit more than one major allelic effect in tight LD. The detected regulatory variants were highly and specifically enriched for activating chromatin structures and allelic transcription factor binding. Integration of MPRA profiles with eQTL/complex trait colocalizations across 114 human traits and diseases identified causal variant sets demonstrating how genetic association signals can manifest through multiple, tightly linked causal variants.